Upaya Meningkatkan Minat Baca dan Menghitung Anak Panti Asuhan Murah Hati Masyarakat Indonesia - Meysa Malika; Fajar Utama Ritonga; Tuti Atika (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
The author conducted a practicum at the Murah Hati Masyarakat Indonesian Orphanage. The practice carried out by the author is to research the problems experienced by orphanage children. The problems experienced by orphanage children are the lack of interest in reading orphanage children so that they experience difficulties in learning and lack of confidence. From these problems, the author is interested and makes a goal to increase the interest in reading and counting orphanage children by creating a mini project, namely a reading corner. The author uses the stages of social groupwork in his research from the preparation stage to the termination stage. After doing all the stages of social groupwork, the results are expected by the author so that the orphanage children can continue their interest in reading and counting so that they do not have difficulties in learning and increase their knowledge and confidence to socialize.